Sewing women : immigrants and the New York City garment industry - Chin, Margaret May, 1962- (Columbia comparative studies on ethnicity and race., 2005)
Many Latino and Chinese women who immigrated to New York City over the past two decades found work in the garment industry-an industry well known for both hiring immigrants and its harsh working conditions. Today the garment industry is one of the largest immigrant employers in New York City and workers in Chinese- and Korean-owned factories produce 70 percent of all manufactured clothing in New York City. Based on extensive interviews with workers and employers, Margaret M. Chin, offers a detailed and complex portrait of the work lives of Chinese and Latino garment workers. Chin, whose m.